A grinding bead for sample processing and a method of making the same
Patent Information
- Application Number
- CN202510403901.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2026-10-23
AI Technical Summary
然而,磁珠法操作步骤较多,需30min左右完成流程,且磁珠法提取时的多次洗涤及洗脱步骤会造成核酸的损失及稀释,可能会降低下游扩增反应的灵敏度
[0153]本发明的主要优点包括:
Smart Images

Figure HDA0005340584880000011 
Figure HDA0005340584880000012 
Figure HDA0005340584880000021
Abstract
Description
Technical Field
[0001] This invention relates to the field of micro and nanomaterial preparation, specifically to a grinding bead for pre-amplification sample processing to achieve extraction-free direct amplification and its preparation method. Background Technology
[0002] Polymerase chain reaction (PCR) is a common nucleic acid molecular diagnostic technique. Its basic principle is to simulate DNA replication inside cells in a reaction chamber, that is, to artificially create semi-conservative conditions for nucleic acid replication, allowing the target DNA to be amplified outside the cell. The routine procedure for molecular diagnostics using PCR technology is: nucleic acid extraction - nucleic acid amplification - nucleic acid detection.
[0003] Nucleic acid extraction refers to the release and purification of nucleic acids from cells or protein coats within a sample. This is typically achieved by disrupting cell walls to release nucleic acid molecules, which are then separated using subsequent separation techniques. Existing extraction methods mainly fall into three categories: solution-based extraction, centrifugal column adsorption, and magnetic bead adsorption. Magnetic bead extraction is currently the most widely used nucleic acid extraction method, and most are now fully automated. This method is flexible and safe. However, it involves numerous steps, requiring approximately 30 minutes to complete, and the multiple washing and elution steps can cause nucleic acid loss and dilution, potentially reducing the sensitivity of downstream amplification reactions. Developing novel materials and nucleic acid sample processing techniques to achieve extraction-free direct nucleic acid amplification while simultaneously meeting the requirements for nucleic acid detection sensitivity is of significant practical importance.
[0004] Therefore, there is an urgent need in this field for a sample processing method and materials that are simple to operate, time-saving, and highly efficient, so as to achieve direct amplification of nucleic acids without extraction. Summary of the Invention
[0005] The purpose of this invention is to provide a grinding bead for processing samples and a method for preparing the same.
[0006] Another objective of this invention is to provide a sample processing method that is simple to operate, time-saving, and highly efficient.
[0007] In a first aspect, the present invention provides a grinding bead, wherein the grinding bead is a spherical or near-spherical inorganic oxide having a porous structure, and the grinding bead is further modified with polar chemical groups; the particle size of the grinding bead is 100 nm to 1000 μm.
[0008] The porous structure is selected from the group consisting of mesopores, micropores, or combinations thereof.
[0009] In another preferred embodiment, the grinding beads have a through-pore or microporous structure.
[0010] In another preferred embodiment, the pore size of the grinding bead is 0.1–50 nm, more preferably 1–10 nm, more preferably 1–5 nm, for example, about 2 nm.
[0011] In another preferred embodiment, the polar group is selected from the group consisting of carboxyl, amino, hydroxyl, or combinations thereof.
[0012] In another preferred embodiment, the inorganic oxide is selected from the group consisting of silicon dioxide, zirconium oxide, ceramics, or glass.
[0013] In another preferred embodiment, the surface area of the grinding beads is 100–1000 m². 2 / g, preferably 300-1000m 2 / g, preferably 400-800m 2 / g, optimal 500-800m 2 / g, for example, about 580m 2 / g or 700m 2 / g.
[0014] In another preferred embodiment, the pore volume of the grinding bead is 0.1–0.5 cm. 3 / g, preferably 0.2–0.5cm 3 / g, preferably 0.2–0.4cm 3 / g, optimally 0.3–0.4cm 3 / g, for example, about 0.33cm 3 / g or 0.35cm 3 / g.
[0015] In another preferred embodiment, the particle size of the grinding beads is 200 nm to 800 μm, more preferably 500 nm to 500 μm.
[0016] In another preferred embodiment, the grinding beads are prepared using a polyethyleneimine derivative as a template agent, the polyethyleneimine derivative being selected from the group consisting of polyethyleneimine, amidated polyethyleneimine, carboxylated polyethyleneimine, or combinations thereof; preferably carboxylated polyethyleneimine.
[0017] In another preferred embodiment, the grinding beads are prepared by calcination using a polyethyleneimine derivative as a template agent.
[0018] In another preferred embodiment, a polyethyleneimine derivative is used as a template agent for the porous structure and reacted with an alkoxysilane to obtain spherical silica. The spherical silica is then calcined to obtain porous grinding beads. The porous grinding beads are then modified with polar chemical groups to obtain the grinding beads.
[0019] In another preferred embodiment, the grinding beads are prepared by the following steps:
[0020] (s1) In the presence of a first solvent, the polyethyleneimine derivative is reacted with an alkoxysilane to obtain spherical silica, wherein the polyethyleneimine derivative is selected from the group consisting of polyethyleneimine, amidated polyethyleneimine, carboxylated polyethyleneimine, or combinations thereof.
[0021] (s2) The spherical silica is calcined at 100–700°C to obtain porous grinding beads; and
[0022] (s3) In the presence of a second solvent, the porous grinding beads react with the first reactant to obtain the grinding beads as described in the first aspect of the present invention;
[0023] The first solvent is selected from the group consisting of water, ethanol, ammonia, or combinations thereof;
[0024] The alkoxysilane is selected from the group consisting of tetramethoxysilane, tetraethoxysilane, propoxysilane, or combinations thereof;
[0025] The second solvent is selected from the group consisting of: water, toluene, ethanol, chloroform, cyclohexane, N,N-dimethylformamide, or combinations thereof;
[0026] The first reactant is selected from the group consisting of: γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), γ-(aminopropyltriethoxysilane (KH-560), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), hydrochloric acid, succinic anhydride, or combinations thereof.
[0027] In a second aspect, the present invention provides a method for preparing grinding beads as described in the first aspect, comprising the steps of:
[0028] (s1) In the presence of a first solvent, the polyethyleneimine derivative is reacted with an alkoxysilane to obtain spherical silica, wherein the polyethyleneimine derivative is selected from the group consisting of polyethyleneimine, amidated polyethyleneimine, carboxylated polyethyleneimine, or combinations thereof.
[0029] (s2) The spherical silica is calcined at 100–700°C to obtain porous grinding beads; and
[0030] (s3) In the presence of a second solvent, the porous grinding beads react with the first reactant to obtain the grinding beads as described in the first aspect of the present invention;
[0031] The first solvent is selected from the group consisting of water, ethanol, ammonia, or combinations thereof;
[0032] The alkoxysilane is selected from the group consisting of tetramethoxysilane, tetraethoxysilane, propoxysilane, or combinations thereof;
[0033] The second solvent is selected from the group consisting of: water, toluene, ethanol, chloroform, cyclohexane, N,N-dimethylformamide, or combinations thereof;
[0034] The first reactant is selected from the group consisting of: γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), γ-(aminopropyltriethoxysilane (KH-560), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), hydrochloric acid, succinic anhydride, or combinations thereof.
[0035] In another preferred embodiment, the polyethyleneimine derivative is prepared by the following steps:
[0036] (z1) Under inert gas conditions, 2-methyl-2-azolinite reacts with an initiator to yield poly(2-methyl-2-azolinite); and
[0037] (z2) The poly(2-methyl-2-azolin) was subjected to hot water hydrolysis and then reacted with an alkenyl amide via a Michael addition reaction to obtain a polyethyleneimine derivative;
[0038] The initiator is selected from the group consisting of: methyl p-toluenesulfonate, trifluoromethanesulfonate, trichloroacetic acid, trifluoroacetic acid, tin chloride, or combinations thereof;
[0039] The alkenylamide is selected from the group consisting of acrylamide, N-butylacrylamide, N-dodecylacrylamide, or combinations thereof.
[0040] In another preferred embodiment, the degree of polymerization of the poly(2-methyl-2-azolin) is 10 to 5000, more preferably 30 to 3000, more preferably 50 to 1000, most preferably 50 to 500, for example about 50 or 300.
[0041] In another preferred embodiment, in step (z1), the mass ratio of the 2-methyl-2-azolinite to the initiator is 50-1000:0.5-5, more preferably 100-1000:1-5, more preferably 100-800:1-3, for example about 110:1.8 or 710:1.8.
[0042] In another preferred embodiment, in step (z1), the reaction is carried out at 80–90°C for 5–20 h, more preferably at 82–88°C for 8–15 h, and even more preferably at 83–87°C for 10–13 h, for example, at 85°C for 12 h.
[0043] In another preferred embodiment, in step (z1), the 2-methyl-2-azolinone is dissolved in anhydrous methyl p-toluenesulfonate at a concentration of 0.1 to 5 g / ml, more preferably 0.1 to 3 g / ml, more preferably 0.3 to 3 g / ml, for example, about 0.3 g / ml, 0.4 g / ml, 2.3 g / ml or 2.4 g / ml.
[0044] In another preferred embodiment, step (z1) includes:
[0045] (z1a) Under inert gas conditions, 2-methyl-2-azolinite reacts with an initiator at 80–90 °C for 5–20 h. After cooling to room temperature, chloroform is added to completely dissolve the solid, followed by the addition of anhydrous ethanol to obtain a white precipitate; and
[0046] (z1b) Separate the white precipitate, add anhydrous diethyl ether, filter, and obtain poly(2-methyl-2-azolin).
[0047] In another preferred embodiment, in step (z1a), the volume of the trichloromethane is 20-80 ml, more preferably 30-60 ml, more preferably 40-60 ml, for example about 50 ml.
[0048] In another preferred embodiment, in steps (z1a) and (z1b), the volume of the anhydrous diethyl ether is 100-300 ml, more preferably 150-250 ml, more preferably 180-230 ml, for example about 200 ml.
[0049] In another preferred embodiment, in step (z2), the hot hydrolysis treatment includes hot hydrolysis of the poly(2-methyl-2-azoline) in a 1-10M hydrochloric acid solution at 80-120°C for 18-36 hours; more preferably, the poly(2-methyl-2-azoline) is hot hydrolyzed in a 3-8M hydrochloric acid solution at 90-110°C for 20-30 hours; more preferably, the poly(2-methyl-2-azoline) is hot hydrolyzed in a 4-6M hydrochloric acid solution at 95-105°C for 20-25 hours; and most preferably, the poly(2-methyl-2-azoline) is hot hydrolyzed in a 5M hydrochloric acid solution at 100°C for 24 hours.
[0050] In another preferred embodiment, the concentration of the poly(2-methyl-2-azolin) in the hydrochloric acid solution is 10-100 g / L, more preferably 30-80 g / L, more preferably 40-60 g / L, for example, about 50 g / L.
[0051] In another preferred embodiment, in step (z2), the Michael addition reaction includes the steps of:
[0052] (z2a) In the presence of a solvent, concentrated ammonia is added dropwise to the hot hydrolyzed poly(2-methyl-2-azolin) to make the pH 8-12 (preferably 8-11, more preferably 9-11, and most preferably 10-11), and the mixture is refrigerated and allowed to stand for 1-5 hours to obtain polyethyleneimine.
[0053] (z2b) The polyethyleneimine and acrylamide are reacted by heating at 50–80°C for 30–50 h, and then added dropwise to ethyl acetate to obtain amidated polyethyleneimine; and
[0054] (z2c) The amidated polyethyleneimine is added to a 3-8 M hydrochloric acid solution, heated and stirred at 90-120°C for 10-15 h, cooled to room temperature, methanol is added, filtered, dissolved in water, and concentrated ammonia is added dropwise to make the pH 8-12 (preferably 8-11, more preferably 9-11, most preferably 10-11), and refrigerated and allowed to stand for 1-5 h to obtain hydroxylated polyethyleneimine.
[0055] In another preferred embodiment, in step (z2a), the solvent comprises methanol.
[0056] In another preferred embodiment, in step (z2b), the mass ratio of the polyethyleneimine to acrylamide is 3-8:1-5, more preferably 3-7:2-4, more preferably 4-6:2-4, for example, about 5:2 or 5:3.
[0057] In another preferred embodiment, in step (z2b), the volume of the ethyl acetate is 100-200 ml, more preferably 120-180 ml, more preferably 130-160 ml, for example about 150 ml.
[0058] In another preferred embodiment, in step (z2c), the concentration of the amidated polyethyleneimine in the hydrochloric acid solution is 10–100 g / L, more preferably 30–80 g / L, more preferably 40–60 g / L, for example, about 50 g / L.
[0059] In another preferred embodiment, in step (z2c), the mixture is heated and stirred at 90–110°C for 10–15 hours, more preferably at 90–110°C for 11–13 hours, for example at 100°C for 12 hours.
[0060] In another preferred embodiment, in steps (z2a) and (z2c), the refrigerator is left to stand for 1 to 4 hours, preferably 2 to 4 hours, for example about 3 hours.
[0061] In another preferred embodiment, step (s1) is carried out in a solution with a pH of 7 to 10, preferably with a pH of 8 to 10, more preferably with a pH of 8.5 to 9.5, for example, with a pH of about 9.
[0062] In another preferred embodiment, in step (s1), the mass-to-volume ratio of the polyethyleneimine derivative to the alkoxysilane is 0.01 to 1 g / ml, more preferably 0.05 to 0.5 g / ml, more preferably 0.1 to 0.3 g / ml, for example, about 0.2 g / ml or 0.1 g / ml.
[0063] In another preferred embodiment, in step (s1), the concentration of the polyethyleneimine derivative is 10 to 100 g / L, more preferably 30 to 80 g / L, more preferably 40 to 60 g / L, for example, about 50 g / L.
[0064] In another preferred embodiment, in step (s1), the polyethyleneimine derivative reacts with the alkoxysilane for 1 to 5 hours, preferably 2 to 4 hours, for example about 3 hours.
[0065] In another preferred embodiment, in step (s2), the spherical silica is calcined for 1 to 5 hours, preferably 2 to 4 hours, for example about 3 hours.
[0066] In another preferred embodiment, in step (s2), the spherical silica is calcined at 200–700°C, more preferably 300–700°C, more preferably 400–700°C, most preferably 500–700°C, for example about 600°C.
[0067] In another preferred embodiment, in step (s3), the second solvent is selected from the group consisting of water, toluene, ethanol, chloroform, cyclohexane, N,N-dimethylformamide, or combinations thereof; preferably, the second solvent includes toluene.
[0068] In another preferred embodiment, step (s3) includes:
[0069] When the grinding beads are hydroxyl-modified grinding beads,
[0070] (s3a) The porous grinding beads are resuspended in 0.01–1 M hydrochloric acid solution, allowed to stand, the precipitate is separated, washed with water until the pH is neutral, and dried overnight to obtain the hydroxyl-modified grinding beads; or
[0071] When the grinding beads are surface-modified amino grinding beads:
[0072] (s3a) The porous grinding beads were resuspended in a 0.01–1 M hydrochloric acid solution, allowed to stand, the precipitate was separated, washed with water until the pH was neutral, and dried overnight to obtain a white powder; and
[0073] (s3b) In the presence of a solvent, a white powder is reacted with γ-(aminopropyltriethoxysilane) at 60–80 °C for 1–5 h to obtain surface-modified amino-based grinding beads; or
[0074] When the grinding beads are grinding beads with carboxyl groups modified on the surface:
[0075] (s3a) The porous grinding beads were resuspended in a 0.01–1 M hydrochloric acid solution, allowed to stand, the precipitate was separated, washed with water until the pH was neutral, and dried overnight to obtain a white powder; and
[0076] (s3b) In the presence of a solvent, a white powder was reacted with γ-(aminopropyltriethoxysilane) at 60-80°C for 1-5 h. After filtration, the mixture was resuspended in N,N-dimethylformamide and succinic anhydride was added and mixed to obtain grinding beads with carboxyl groups modified on the surface.
[0077] In another preferred embodiment, in step (s3a), the concentration of the porous grinding beads in the hydrochloric acid solution is 1 to 50 g / L, more preferably 5 to 30 g / L, more preferably 5 to 20 g / L, for example, about 10 g / L.
[0078] In another preferred embodiment, in step (s3), the mass ratio of the porous grinding beads to the first reactant is 0.1–5:0.01–1, more preferably 0.5–3:0.05–1, more preferably 0.5–2:0.1–0.5, for example, about 1:0.2 or 1:0.3.
[0079] In another preferred embodiment, step (s3b) is performed in an environment in the presence of an inert gas.
[0080] In another preferred embodiment, when the grinding beads are surface-modified carboxyl grinding beads, in step (s3b), the mass ratio of γ-(aminopropyltriethoxysilane) to succinic anhydride is 1-5:1-5, more preferably 1-5:1-3, more preferably 1-3:1, for example, 2:1.
[0081] In a third aspect, the invention provides the use of the grinding beads as described in the first aspect for sample processing prior to nucleic acid amplification.
[0082] In another preferred embodiment, the grinding beads are also used to extract nucleic acids from the sample.
[0083] In a fourth aspect, the present invention provides a kit comprising grinding beads as described in the first aspect of the present invention.
[0084] In another preferred embodiment, the kit is used for sample processing prior to nucleic acid amplification and is further used to extract nucleic acids from samples containing nucleic acids.
[0085] In another preferred embodiment, the kit further includes a washing solution and / or an elution solution.
[0086] In a fifth aspect, the present invention provides a sample processing method, comprising the steps of:
[0087] The grinding beads as described in the first aspect of the present invention are brought into contact with the sample for sample processing before nucleic acid amplification.
[0088] In another preferred embodiment, the sample contains nucleic acid.
[0089] In another preferred embodiment, the concentration of the grinding beads is 0.01 to 10 g / mL, more preferably 0.1 to 5 g / mL, and even more preferably 0.1 to 1 g / mL, for example, about 0.4 g / mL.
[0090] In another preferred embodiment, the nucleic acid release rate of the method is ≥40%, more preferably ≥50%, and even more preferably ≥60%.
[0091] In another preferred embodiment, nucleic acids are extracted from the sample using the method described above.
[0092] It should be understood that, within the scope of this invention, the above-described technical features of this invention and the technical features specifically described below (such as in the embodiments) can be combined with each other to form new or preferred technical solutions. Due to space limitations, they will not be described in detail here. Attached Figure Description
[0093] Figure 1 The diagram shows the technology roadmap for preparing grinding beads.
[0094] Figure 2 The NMR spectrum of the poly(2-methyl-2-azolin) prepared in Example 1 is shown, with a degree of polymerization of 50 and a PDI of ≤1.3.
[0095] Figure 3 Transmission electron microscopy (TEM) images and particle size distribution diagrams of the carboxyl-modified porous grinding beads prepared in Example 1 are shown.
[0096] Figure 4 The BET test data of the spherical silica (before calcination) prepared in Example 1 are shown.
[0097] Figure 5 The BET test data of the carboxyl-modified porous grinding beads prepared in Example 1 are shown.
[0098] Figure 6 The TGA curves (35°C-800°C) of the spherical silica prepared in step 3 of Example 1 are shown.
[0099] Figure 7 The NMR spectrum of the poly(2-methyl-2-azolin) prepared in Example 2 is shown, with a degree of polymerization of 300 and a PDI of ≤1.3.
[0100] Figure 8The image shows a scanning electron microscope (SEM) image and particle size distribution of the amino-modified porous grinding beads prepared in Example 2.
[0101] Figure 9 The BET test data of the amino-modified porous grinding beads prepared in Example 2 are shown.
[0102] Figure 10 The image shows a scanning electron microscope (SEM) image and particle size distribution of the silanol-modified porous grinding beads prepared in Example 3.
[0103] Figure 11 The photograph shows the reaction phenomenon of preparing spherical silica from polyethyleneimine in Comparative Example 1 overnight.
[0104] Figure 12 The photograph shows the reaction phenomenon of preparing spherical silica by amidation of polyethyleneimine in Comparative Example 2 after overnight exposure. Detailed Implementation
[0105] Through extensive and in-depth research, and after numerous experiments and screenings, the inventors unexpectedly discovered for the first time a grinding bead for sample processing and its preparation method. Specifically, the grinding bead is a spherical or near-spherical inorganic oxide with a porous structure, and it is further modified with polar chemical groups. The grinding bead of this invention has abundant micropores and mesopores on its interior and surface, increasing its contact area with the solution; it also provides additional functions such as filtering impurities and adsorbing proteins, improving the ability to remove impurities and inhibitors. The grinding bead of this invention is made of safe materials, has a stable structure, and a uniform particle size distribution, making it suitable for a wide range of applications. This invention was completed based on these findings.
[0106] the term
[0107] To facilitate understanding of the invention, certain technical and scientific terms are specifically defined below. Unless otherwise expressly defined herein, all other technical and scientific terms used herein have the meanings commonly understood by one of ordinary skill in the art to which this invention pertains. Before describing the invention, it should be understood that the invention is not limited to the specific methods and experimental conditions described, as such methods and conditions can vary. It should also be understood that the terminology used herein is intended only to describe particular embodiments and is not intended to be restrictive; the scope of the invention will be limited only by the appended claims.
[0108] As used herein, the term “comprising” or its variations such as “including” or “comprising” are understood to include the said element or component without excluding other elements or other components.
[0109] The term “about” can refer to a value or composition within an acceptable margin of error for a particular value or composition as determined by a person skilled in the art, depending in part on how the value or composition is measured or determined. For example, as used herein, the expression “about 100” includes all values between 99 and 101 (e.g., 99.1, 99.2, 99.3, 99.4, etc.).
[0110] As used herein, unless otherwise stated, any concentration range, percentage range, proportion range, or integer range shall be understood to include any integer value within the range and, where appropriate, its fractional value (e.g., one-tenth and one-hundredth of an integer).
[0111] As used herein, the term “and / or” refers to and covers any and all possible combinations of one or more of the related listed items.
[0112] Micropores and mesopores
[0113] Pores with a diameter of less than 2 nanometers are called micropores; porous material structures with a diameter between 2 nanometers and 50 nanometers are called mesopores (according to the definition of the International Union of Pure and Applied Chemistry (IUPAC)).
[0114] The grinding beads of the present invention
[0115] The grinding beads of the present invention refer to spherical or near-spherical inorganic oxides with a porous structure, and the grinding beads are further modified with polar chemical groups; the particle size of the grinding beads is 100 nm to 1000 μm;
[0116] The porous structure is selected from the group consisting of mesopores, micropores, or combinations thereof.
[0117] In a preferred embodiment, the polar group is selected from the group consisting of carboxyl, amino, hydroxyl, or combinations thereof. In a preferred embodiment, the inorganic oxide is selected from the group consisting of silicon dioxide, zirconium oxide, ceramic, or glass. The grinding beads of the present invention are porous grinding beads with an inorganic material body, which are safe and structurally stable, and can provide strong impact force in practical applications (such as during ultrasonic vibration treatment).
[0118] In a preferred embodiment, the surface area of the grinding beads is 100–1000 m². 2 / g, preferably 300-1000m 2 / g, preferably 400-800m 2 / g, optimal 500-800m 2 / g, for example, about 580m 2 / g or 700m 2 / g. In a preferred embodiment, the pore volume of the grinding beads is 0.1–0.5 cm³. 3 / g, preferably 0.2–0.5cm 3 / g, preferably 0.2–0.4cm 3 / g, optimally 0.3–0.4cm 3 / g, for example, about 0.33cm 3 / g or 0.35cm 3 / g. The grinding beads of the present invention contain abundant micropores and mesopores on their interior and surface. These porous morphologies have excellent effects on increasing contact with the solution and filtering impurities.
[0119] In a preferred embodiment, the grinding beads are prepared using a polyethyleneimine derivative as a template agent, the polyethyleneimine derivative being selected from the group consisting of polyethyleneimine, amidated polyethyleneimine, carboxylated polyethyleneimine, or combinations thereof; preferably carboxylated polyethyleneimine. The polymeric precursor of the polyethyleneimine derivative is poly(2-methyl-2-azoline), with a polymerization degree of 10–5000, more preferably 30–3000, more preferably 50–1000, and most preferably 50–500, for example about 50 or 300. Those skilled in the art can prepare grinding beads of the present invention with different particle sizes by using poly(2-methyl-2-azoline) with different degrees of polymerization.
[0120] In a preferred embodiment, a polyethyleneimine derivative is used as a template agent for the porous structure and reacted with an alkoxysilane to obtain spherical silica. The spherical silica is then calcined to obtain porous grinding beads. The porous grinding beads are then modified with polar chemical groups to obtain the grinding beads.
[0121] The method of the present invention
[0122] The method of the present invention is used to prepare the grinding beads of the present invention, comprising the following steps:
[0123] (s1) In the presence of a first solvent, the polyethyleneimine derivative is reacted with an alkoxysilane to obtain spherical silica, wherein the polyethyleneimine derivative is selected from the group consisting of polyethyleneimine, amidated polyethyleneimine, carboxylated polyethyleneimine, or combinations thereof.
[0124] (s2) The spherical silica is calcined at 100–700°C to obtain porous grinding beads; and
[0125] (s3) In the presence of a second solvent, the porous grinding beads react with the first reactant to obtain the grinding beads as described in the first aspect of the present invention;
[0126] The first solvent is selected from the group consisting of water, ethanol, ammonia, or combinations thereof;
[0127] The alkoxysilane is selected from the group consisting of tetramethoxysilane, tetraethoxysilane, propoxysilane, or combinations thereof;
[0128] The second solvent is selected from the group consisting of: water, toluene, ethanol, chloroform, cyclohexane, N,N-dimethylformamide, or combinations thereof;
[0129] The first reactant is selected from the group consisting of: γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), γ-(aminopropyltriethoxysilane (KH-560), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), hydrochloric acid, succinic anhydride, or combinations thereof.
[0130] In a preferred embodiment, the polyethyleneimine derivative is prepared by the following steps:
[0131] (z1) Under inert gas conditions, 2-methyl-2-azolinite reacts with an initiator to yield poly(2-methyl-2-azolinite); and
[0132] (z2) The poly(2-methyl-2-azolin) was subjected to hot water hydrolysis and then reacted with an alkenyl amide via a Michael addition reaction to obtain a polyethyleneimine derivative;
[0133] The initiator is selected from the group consisting of: methyl p-toluenesulfonate, trifluoromethanesulfonate, trichloroacetic acid, trifluoroacetic acid, tin chloride, or combinations thereof;
[0134] The alkenylamide is selected from the group consisting of acrylamide, N-butylacrylamide, N-dodecylacrylamide, or combinations thereof.
[0135] In a preferred embodiment, the degree of polymerization of the poly(2-methyl-2-azolin) is 10 to 5000, more preferably 30 to 3000, more preferably 50 to 1000, most preferably 50 to 500, for example about 50 or 300.
[0136] In a preferred embodiment, step (s3) includes:
[0137] When the grinding beads are hydroxyl-modified grinding beads,
[0138] (s3a) The porous grinding beads are resuspended in 0.01–1 M hydrochloric acid solution, allowed to stand, the precipitate is separated, washed with water until the pH is neutral, and dried overnight to obtain the hydroxyl-modified grinding beads; or
[0139] When the grinding beads are surface-modified amino grinding beads:
[0140] (s3a) The porous grinding beads were resuspended in a 0.01–1 M hydrochloric acid solution, allowed to stand, the precipitate was separated, washed with water until the pH was neutral, and dried overnight to obtain a white powder; and
[0141] (s3b) In the presence of a solvent, a white powder is reacted with γ-(aminopropyltriethoxysilane) at 60–80 °C for 1–5 h to obtain surface-modified amino-based grinding beads; or
[0142] When the grinding beads are grinding beads with carboxyl groups modified on the surface:
[0143] (s3a) The porous grinding beads were resuspended in a 0.01–1 M hydrochloric acid solution, allowed to stand, the precipitate was separated, washed with water until the pH was neutral, and dried overnight to obtain a white powder; and
[0144] (s3b) In the presence of a solvent, a white powder was reacted with γ-(aminopropyltriethoxysilane) at 60-80°C for 1-5 h. After filtration, the mixture was resuspended in N,N-dimethylformamide and succinic anhydride was added and mixed to obtain grinding beads with carboxyl groups modified on the surface.
[0145] Methods for processing samples
[0146] The present invention also provides a method for processing samples, comprising the steps of:
[0147] The grinding beads as described in the first aspect of the present invention are brought into contact with the sample for sample processing before nucleic acid amplification.
[0148] In a preferred embodiment, the sample contains nucleic acids.
[0149] In a preferred embodiment, nucleic acids are extracted from a sample using the method described above.
[0150] In a preferred embodiment, the concentration of the grinding beads is 0.01 to 10 g / mL, more preferably 0.1 to 5 g / mL, and even more preferably 0.1 to 1 g / mL, for example, about 0.4 g / mL.
[0151] In a preferred embodiment, the nucleic acid release rate of the method is ≥40%, more preferably ≥50%, and even more preferably ≥60%.
[0152] In this invention, the sample processing method of this invention can achieve the effect of direct amplification of nucleic acid without extraction. After processing, the sample can be directly used for nucleic acid amplification.
[0153] The main advantages of this invention include:
[0154] 1. The grinding beads of the present invention contain abundant micropores and mesopores on their interior and surface. These porous morphologies have excellent effects on increasing contact with the solution and filtering impurities.
[0155] 2. The grinding beads of the present invention are porous grinding beads, and the body is made of inorganic material. The material is safe and the structure is stable. In practical applications (such as ultrasonic vibration treatment), they can provide a strong collision effect.
[0156] 3. The organic modification layer on the surface of the grinding beads of the present invention is covalently coupled, which is stable and will not detach.
[0157] 4. The grinding beads of the present invention have a wide range of adjustable particle size, a narrow particle size distribution, and a more regular morphology, making the product suitable for a wide range of applications.
[0158] 5. The porous structure and modification layer on the surface of the grinding beads of the present invention provide additional functions such as impurity filtration and protein adsorption, thereby increasing the ability to remove impurities and inhibitors.
[0159] 6. In the preparation method of the grinding beads of the present invention, the template agent used has a simple and mature synthesis route, and the synthesized polymer template agent has a low PDI, so as to form grinding beads with more uniform particle size distribution and regular morphology.
[0160] 7. In the preparation method of the grinding beads of the present invention, the particle size of the grinding beads can be changed by adjusting the degree of polymerization of the template agent, and grinding beads with suitable particle size can be prepared according to different application scenarios.
[0161] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions, such as those described in Sambrook et al., Molecular Cloning: A Laboratory Manual (New York: Cold Spring Harbor Laboratory Press, 1989), or as recommended by the manufacturer. Unless otherwise stated, percentages and parts are by weight.
[0162] Example 1
[0163] This embodiment provides a method for synthesizing grinding beads, including the preparation of a polymer precursor, a template agent, porous grinding beads, and a surface modification layer. The grinding beads are silica with a particle size of approximately 0.9 μm and a surface carboxyl group modified. The main preparation steps are as follows:
[0164] Step 1: Synthesis of the polymer precursor: Under nitrogen protection, 11.3 g of 2-methyl-2-azolinite monomer was dissolved in 30 mL of anhydrous methyl p-toluenesulfonate, followed by the addition of 0.18 g of methyl p-toluenesulfonate. The mixture was heated under reflux at 85 °C for 12 h. The mixture was then cooled to room temperature, and 50 mL of chloroform was added. After complete dissolution, the mixture was slowly added to 200 mL of anhydrous diethyl ether. The mixture was allowed to stand until a white precipitate appeared, then centrifuged, and the filtrate was removed. The white precipitate was again added to 200 mL of anhydrous diethyl ether, allowed to stand until a white precipitate appeared, then centrifuged, and the filtrate was removed. The collected white precipitate was dried under vacuum to obtain a white powder, which is poly(2-methyl-2-azolinite) with a degree of polymerization of 50.
[0165] Figure 2 The NMR spectrum of poly(2-methyl-2-azolin).
[0166] Step 2: Synthesis of template agent: Add 5g of poly(2-methyl-2-azolin) to 100mL of 5M hydrochloric acid solution, heat and stir at 100℃ for 12h, and after the reaction solution cools to room temperature, slowly add 300mL of methanol, stir thoroughly and filter. Dissolve the white solid obtained in water again. After complete dissolution, adjust the pH to 10 by adding concentrated ammonia dropwise. Place the solution in a refrigerator and let it stand for 3 hours. Filter the white precipitate again, wash with ultrapure water until the pH is close to neutral, and finally wash twice with 100mL of acetone. The final white solid obtained is polyethyleneimine.
[0167] In a 50 mL round-bottom flask, 14 mL of N,N-dimethylformamide, 5 g of polyethyleneimine, and 2.2 g of acrylamide were added sequentially. The mixture was heated under reflux at 60 °C for 48 h. The reaction solution was diluted and added dropwise to 150 mL of ethyl acetate to obtain a white precipitate. The white precipitate was centrifuged and washed twice with ethyl acetate. The precipitate was then dried in a drying oven for 3 hours to obtain amidated polyethyleneimine.
[0168] Add 5g of amidated polyethyleneimine to 100mL of 5M hydrochloric acid solution. Heat and stir at 100℃ for 12h. After the reaction solution cools to room temperature, slowly add 300mL of methanol. After stirring thoroughly, filter. Dissolve the obtained white solid in water again. After complete dissolution, adjust the pH to 10 by adding concentrated ammonia dropwise. Place the solution in a refrigerator and let it stand for 3 hours. Filter the white precipitate again and wash with deionized water until the pH is close to neutral. Finally, wash twice with 100mL of acetone. The final white solid is carboxylated polyethyleneimine.
[0169] Step 3: Preparation of grinding beads: Dissolve 0.5g of carboxylated polyethyleneimine in 100mL of ultrapure water. After complete dissolution, adjust the pH to 9 by adding 1M sodium hydroxide aqueous solution. Under stirring conditions, slowly add 2.5mL of tetramethoxysilane and stir at room temperature for 3h to obtain a large amount of white precipitate. Separate the white precipitate by centrifugation, wash it once with ethanol, wash it twice with ultrapure water, and dry it to obtain spherical silica.
[0170] Step 4: Preparation of porous grinding beads: Place 3g of spherical silica powder into a ceramic crucible, place the ceramic crucible into a muffle furnace, and calcine at 600℃ for 3h. After returning to room temperature, collect the calcined powder to obtain porous grinding beads.
[0171] Step 5: Preparation of carboxylated porous grinding beads: Take 1g of porous grinding beads and resuspend them in 100mL of 0.1M hydrochloric acid solution. Let them stand for 1h, then centrifuge to collect the precipitate. Wash with ultrapure water until the pH is neutral, and then dry in a drying oven overnight.
[0172] The dried white powder was resuspended in 50 mL of toluene and fully dispersed. 0.2 g of γ-(aminopropyltriethoxysilane) was added, and the mixture was heated to 70 °C and stirred for 3 h. After the reaction was completed, the solvent was removed by centrifugation, and the mixture was washed once with toluene and twice with N,N-dimethylformamide.
[0173] The cleaned white powder was resuspended in 50 mL of N,N-dimethylformamide, and 0.1 g of succinic anhydride was added. The mixture was stirred for 3 h under nitrogen protection, centrifuged to collect the precipitate, washed twice with N,N-dimethylformamide and twice with ultrapure water, and dried overnight in a drying oven to obtain carboxyl-modified porous grinding beads.
[0174] Figure 3 Transmission electron microscopy (TEM) images and particle size distribution diagrams of porous grinding beads with surface-modified carboxyl groups are shown.
[0175] Figure 4 The BET test data for spherical silica (before calcination) are shown. Figure 5 The BET test data for porous grinding beads with surface-modified carboxyl groups are shown. Figure 6 The TAG curves of the spherical silica are shown, indicating that the grinding beads of the present invention are completely calcined.
[0176] Example 2
[0177] This embodiment provides a method for synthesizing grinding beads, including the preparation of a polymer precursor, a template agent, porous grinding beads, and a surface modification layer. The grinding beads are amino-modified silica with a particle size of approximately 2.6 μm. The main preparation steps are as follows:
[0178] Step 1: Synthesis of the polymer precursor: Under nitrogen protection, 71.3 g of 2-methyl-2-azolinite monomer was dissolved in 30 mL of anhydrous methyl p-toluenesulfonate, followed by the addition of 0.18 g of methyl p-toluenesulfonate. The mixture was heated under reflux at 85 °C for 12 h. The mixture was then cooled to room temperature, and 50 mL of chloroform was added. After complete dissolution, the mixture was slowly added to 200 mL of anhydrous diethyl ether. The mixture was allowed to stand until a white precipitate appeared, then centrifuged, and the filtrate was removed. The white precipitate was again added to 200 mL of anhydrous diethyl ether, allowed to stand until a white precipitate appeared, then centrifuged, and the filtrate was removed. The collected white precipitate was dried under vacuum to obtain a white powder, which is poly(2-methyl-2-azolinite) with a degree of polymerization of 300.
[0179] Figure 7 The NMR spectrum of poly(2-methyl-2-azolin) (degree of polymerization 300) is shown.
[0180] Step 2: Synthesis of template agent: Add 5g of poly(2-methyl-2-azolin) to 100mL of 5M hydrochloric acid solution, heat and stir at 100℃ for 12h, and after the reaction solution cools to room temperature, slowly add 300mL of methanol, stir thoroughly and filter. Dissolve the white solid obtained in water again. After complete dissolution, adjust the pH to 10 by adding concentrated ammonia dropwise. Place the solution in a refrigerator and let it stand for 3 hours. Filter the white precipitate again, wash with ultrapure water until the pH is close to neutral, and finally wash twice with 100mL of acetone. The final white solid obtained is polyethyleneimine.
[0181] In a 50 mL round-bottom flask, 14 mL of N,N-dimethylformamide, 5 g of polyethyleneimine, and 3.2 g of acrylamide were added sequentially. The mixture was heated under reflux at 60 °C for 48 h. The reaction solution was diluted and added dropwise to 150 mL of ethyl acetate to obtain a white precipitate. The white precipitate was centrifuged and washed twice with ethyl acetate. The precipitate was then dried in a drying oven for 3 h to obtain amidated polyethyleneimine.
[0182] Add 5g of amidated polyethyleneimine to 100mL of 5M hydrochloric acid solution. Heat and stir at 100℃ for 12h. After the reaction solution cools to room temperature, slowly add 300mL of methanol. After stirring thoroughly, filter. Dissolve the obtained white solid in water again. After complete dissolution, adjust the pH to 10 by adding concentrated ammonia dropwise. Place the solution in a refrigerator and let it stand for 3 hours. Filter the white precipitate again and wash with deionized water until the pH is close to neutral. Finally, wash twice with 100mL of acetone. The final white solid is carboxylated polyethyleneimine.
[0183] Step 3: Preparation of grinding beads: Dissolve 0.5g of carboxylated polyethyleneimine in 100mL of ultrapure water. After complete dissolution, adjust the pH to 9 by adding 1M sodium hydroxide aqueous solution. Under stirring conditions, slowly add 2.5mL of tetramethoxysilane and stir at room temperature for 3h to obtain a large amount of white precipitate. Separate the white precipitate by centrifugation, wash it once with ethanol, wash it twice with ultrapure water, and dry it to obtain spherical silica.
[0184] Step 4: Preparation of porous grinding beads: Place 3g of spherical silica powder into a ceramic crucible, place the ceramic crucible into a muffle furnace, and calcine at 600℃ for 3h. After returning to room temperature, collect the calcined powder to obtain porous grinding beads.
[0185] Step 5: Preparation of ammoniated porous grinding beads: Take 1g of porous grinding beads and resuspend them in 100mL of 0.1M hydrochloric acid solution. Let them stand for 1h, then centrifuge to collect the precipitate. Wash with ultrapure water until the pH is neutral, and then dry in a drying oven overnight.
[0186] The dried white powder was resuspended in 50 mL of toluene and fully dispersed. 0.3 g of N-(6-aminoethyl)aminomethyltriethoxysilane was added, and the mixture was heated to 70 °C and stirred for 3 h. After the reaction was completed, the solvent was removed by centrifugation. The mixture was washed once with toluene, twice with N,N-dimethylformamide, and twice with ultrapure water. After drying in a drying oven overnight, amino-modified porous grinding beads were obtained.
[0187] Figure 8 Scanning electron microscope (SEM) images and particle size distribution maps of porous grinding beads with amino-modified surfaces are shown. Figure 9 The BET test data for porous grinding beads with amino-modified surfaces are shown.
[0188] Example 3
[0189] This embodiment provides a method for synthesizing grinding beads, including the preparation of a polymer precursor, a template agent, porous grinding beads, and a surface modification layer. The grinding beads are silicon dioxide with a particle size of approximately 3 μm and a surface of silanol groups. The main preparation steps are as follows:
[0190] Step 1: Synthesis of the polymer precursor: Under nitrogen protection, 71.3 g of 2-methyl-2-azolinite monomer was dissolved in 30 mL of anhydrous methyl p-toluenesulfonate, followed by the addition of 0.18 g of methyl p-toluenesulfonate. The mixture was heated under reflux at 85 °C for 12 h. The mixture was then cooled to room temperature, and 50 mL of chloroform was added. After complete dissolution, the mixture was slowly added to 200 mL of anhydrous diethyl ether. The mixture was allowed to stand until a white precipitate appeared, then centrifuged, and the filtrate was removed. The white precipitate was again added to 200 mL of anhydrous diethyl ether, allowed to stand until a white precipitate appeared, then centrifuged, and the filtrate was removed. The collected white precipitate was dried under vacuum to obtain a white powder, which is poly(2-methyl-2-azolinite) with a degree of polymerization of 300.
[0191] Step 2: Synthesis of template agent: Add 5g of poly(2-methyl-2-azolin) to 100mL of 5M hydrochloric acid solution, heat and stir at 100℃ for 12h, and after the reaction solution cools to room temperature, slowly add 300mL of methanol, stir thoroughly and filter. Dissolve the white solid obtained in water again. After complete dissolution, adjust the pH to 10 by adding concentrated ammonia dropwise. Place the solution in a refrigerator and let it stand for 3 hours. Filter the white precipitate again, wash with ultrapure water until the pH is close to neutral, and finally wash twice with 100mL of acetone. The final white solid obtained is polyethyleneimine.
[0192] In a 50 mL round-bottom flask, 14 mL of N,N-dimethylformamide, 5 g of polyethyleneimine, and 3.2 g of acrylamide were added sequentially. The mixture was heated under reflux at 60 °C for 48 h. The reaction solution was diluted and added dropwise to 150 mL of ethyl acetate to obtain a white precipitate. The white precipitate was centrifuged and washed twice with ethyl acetate. The precipitate was then dried in a drying oven for 3 h to obtain amidated polyethyleneimine.
[0193] Add 5g of amidated polyethyleneimine to 100mL of 5M hydrochloric acid solution. Heat and stir at 100℃ for 12h. After the reaction solution cools to room temperature, slowly add 300mL of methanol. After stirring thoroughly, filter. Dissolve the obtained white solid in water again. After complete dissolution, adjust the pH to 10 by adding concentrated ammonia dropwise. Place the solution in a refrigerator and let it stand for 3 hours. Filter the white precipitate again and wash with deionized water until the pH is close to neutral. Finally, wash twice with 100mL of acetone. The final white solid is carboxylated polyethyleneimine.
[0194] Step 3: Preparation of grinding beads: Dissolve 0.5g of carboxylated polyethyleneimine in 100mL of ultrapure water. After complete dissolution, adjust the pH to 9 by adding 1M sodium hydroxide aqueous solution. Under stirring conditions, slowly add 5mL of tetramethoxysilane and stir at room temperature for 3h to obtain a large amount of white precipitate. Separate the white precipitate by centrifugation, wash it once with ethanol, wash it twice with ultrapure water, and dry it to obtain spherical silica.
[0195] Step 4: Preparation of porous grinding beads: Place 3g of spherical silica powder into a ceramic crucible, place the ceramic crucible into a muffle furnace, and calcine at 600℃ for 3h. After returning to room temperature, collect the calcined powder to obtain porous grinding beads.
[0196] Step 5: Preparation of porous grinding beads with silanol surface: Take 1g of porous grinding beads and resuspend them in 100mL of 1M hydrochloric acid solution, sonicate for 10min, let stand for 1h, then centrifuge to collect the precipitate, wash three times with ultrapure water, and dry in a drying oven overnight to obtain porous grinding beads with abundant silanol surface.
[0197] Figure 10 Scanning electron microscope (SEM) images and particle size distribution maps of porous grinding beads with surface-modified silanol groups are shown.
[0198] Comparative Example 1
[0199] This embodiment provides a method for synthesizing grinding beads, including the preparation of polymer precursors, template agents, and grinding beads, mainly comprising the following preparation steps:
[0200] Step 1: Synthesis of the polymer precursor: Under nitrogen protection, 11.3 g of 2-methyl-2-azolinite monomer was dissolved in 30 mL of anhydrous methyl p-toluenesulfonate, followed by the addition of 0.18 g of methyl p-toluenesulfonate. The mixture was heated under reflux at 85 °C for 12 h. The mixture was then cooled to room temperature, and 50 mL of chloroform was added. After complete dissolution, the mixture was slowly added to 200 mL of anhydrous diethyl ether. The mixture was allowed to stand until a white precipitate appeared, then centrifuged, and the filtrate was removed. The white precipitate was again added to 200 mL of anhydrous diethyl ether, allowed to stand until a white precipitate appeared, then centrifuged, and the filtrate was removed. The collected white precipitate was dried under vacuum to obtain a white powder, which is poly(2-methyl-2-azolinite) with a degree of polymerization of 50.
[0201] Step 2: Synthesis of template agent: Add 5g of poly(2-methyl-2-azolin) to 100mL of 5M hydrochloric acid solution, heat and stir at 100℃ for 12h, and after the reaction solution cools to room temperature, slowly add 300mL of methanol, stir thoroughly and filter. Dissolve the white solid obtained in water again. After complete dissolution, adjust the pH to 10 by adding concentrated ammonia dropwise. Place the solution in a refrigerator and let it stand for 3 hours. Filter the white precipitate again, wash with ultrapure water until the pH is close to neutral, and finally wash twice with 100mL of acetone. The final white solid obtained is polyethyleneimine.
[0202] Step 3: Preparation of grinding beads: Dissolve 0.5g of polyethyleneimine in 100mL of ultrapure water. After complete dissolution, slowly add 2.5mL of tetramethoxysilane under stirring. Stir overnight at room temperature. The solution gels and the solid cannot be separated, proving that the preparation of spherical silica using polyethyleneimine as a template agent was unsuccessful. Figure 11 ).
[0203] Comparative Example 2
[0204] This embodiment provides a method for synthesizing grinding beads, including the preparation of polymer precursors, template agents, and grinding beads, mainly comprising the following preparation steps:
[0205] Step 1: Synthesis of the polymer precursor: Under nitrogen protection, 11.3 g of 2-methyl-2-azolinite monomer was dissolved in 30 mL of anhydrous methyl p-toluenesulfonate, followed by the addition of 0.18 g of methyl p-toluenesulfonate. The mixture was heated under reflux at 85 °C for 12 h. The mixture was then cooled to room temperature, and 50 mL of chloroform was added. After complete dissolution, the mixture was slowly added to 200 mL of anhydrous diethyl ether. The mixture was allowed to stand until a white precipitate appeared, then centrifuged, and the filtrate was removed. The white precipitate was again added to 200 mL of anhydrous diethyl ether, allowed to stand until a white precipitate appeared, then centrifuged, and the filtrate was removed. The collected white precipitate was dried under vacuum to obtain a white powder, which is poly(2-methyl-2-azolinite) with a degree of polymerization of 50.
[0206] Step 2: Synthesis of template agent: Add 5g of poly(2-methyl-2-azolin) to 100mL of 5M hydrochloric acid solution, heat and stir at 100℃ for 12h, and after the reaction solution cools to room temperature, slowly add 300mL of methanol, stir thoroughly and filter. Dissolve the white solid obtained in water again. After complete dissolution, adjust the pH to 10 by adding concentrated ammonia dropwise. Place the solution in a refrigerator and let it stand for 3 hours. Filter the white precipitate again, wash with ultrapure water until the pH is close to neutral, and finally wash twice with 100mL of acetone. The final white solid obtained is polyethyleneimine.
[0207] In a 50 mL round-bottom flask, 14 mL of N,N-dimethylformamide, 5 g of polyethyleneimine, and 2.2 g of acrylamide were added sequentially. The mixture was heated under reflux at 60 °C for 48 h. The reaction solution was diluted and added dropwise to 150 mL of ethyl acetate to obtain a white precipitate. The white precipitate was centrifuged and washed twice with ethyl acetate. The precipitate was then dried in a drying oven for 3 hours to obtain amidated polyethyleneimine.
[0208] Step 3: Preparation of grinding beads: Dissolve 0.1g of amidated polyethyleneimine in 20mL of ultrapure water. After complete dissolution, slowly add 0.5mL of tetramethoxysilane under stirring. Stir overnight at room temperature. The solution becomes clear and unchanged, proving that spherical silica cannot be prepared using amidated polyethyleneimine as a template agent. Figure 12 ).
[0209] Example of effect
[0210] To evaluate the nucleic acid release and impurity removal capabilities of the porous grinding beads of this invention, solid glass beads and quartz sand were selected for comparative testing. Oropharyngeal swabs were added to physiological saline, and H1N1 pseudovirus was added to simulate the sample test. The amounts of the above materials added are shown in Table 16.
[0211] Table 16
[0212] 1 Porous grinding beads 0.8 2 solid glass beads 0.8 3 Quartz sand 0.8 4 Non-grinding filter beads 5 Nucleic acid extraction
[0213] The specific operating procedure is as follows:
[0214] 1. Sample processing
[0215] Take samples of influenza A virus
[0216] 2. Sample pretreatment for amplification
[0217] Take 8 mL of preservation solution, add it to 4 sampling swabs, and mix thoroughly. Aliquot the prepared preservation solution into 2 mL tubes, and add an equal amount of influenza A sample to each tube. Process 4 tubes according to the table above, and use the remaining tube without the grinding filter beads as a control, and take 200 μL from the control tube as the sample for nucleic acid extraction.
[0218] 3. Sample testing
[0219] The above samples were tested using an influenza A virus / influenza B virus nucleic acid detection kit (fluorescent PCR method).
[0220] The results are shown in Table 17.
[0221] Table 17
[0222] 1 Porous grinding beads 0.8 28.87 29.17 29.02 63.63% 2 solid glass beads 0.8 30.23 30.34 30.29 26.52% 3 Quartz sand 0.8 30.11 30.08 30.10 30.25% 4 Non-grinding filter beads NoCt NoCt / / 5 Nucleic acid extraction 27.31 27.37 27.34 /
[0223] Based on the above results, porous grinding beads can effectively improve the amplification effect after the release of nucleic acid from the sample.
[0224] All documents mentioned in this invention are incorporated herein by reference as if each document were individually incorporated by reference. Furthermore, it should be understood that after reading the foregoing teachings of this invention, those skilled in the art can make various alterations or modifications to this invention, and these equivalent forms also fall within the scope defined by the appended claims.
Claims
1. A grinding bead, characterized in that, The grinding beads are spherical or near-spherical inorganic oxides with a porous structure, and the grinding beads are also modified with polar chemical groups; the particle size of the grinding beads is 100nm to 1000μm. The porous structure is selected from the group consisting of mesopores, micropores, or combinations thereof.
2. The grinding bead as described in claim 1, characterized in that, The polar group is selected from the group consisting of carboxyl, amino, hydroxyl, or combinations thereof.
3. The grinding bead as described in claim 1, characterized in that, The inorganic oxide is selected from the group consisting of silicon dioxide, zirconium oxide, ceramics, or glass.
4. The grinding bead as described in claim 1, characterized in that, The surface area of the grinding beads is 100-1000 m². 2 / g, preferably 300-1000m 2 / g, preferably 400-800m 2 / g, optimal 500-800m 2 / g.
5. The grinding bead as described in claim 1, characterized in that, The pore volume of the grinding beads is 0.1–0.5 cm. 3 / g, preferably 0.2–0.5cm 3 / g, preferably 0.2–0.4cm 3 / g, optimally 0.3–0.4cm 3 / g.
6. The grinding bead as described in claim 1, characterized in that, The grinding beads are prepared using a polyethyleneimine derivative as a template agent, wherein the polyethyleneimine derivative is selected from the group consisting of polyethyleneimine, amidated polyethyleneimine, carboxylated polyethyleneimine, or combinations thereof.
7. A method for preparing the grinding beads as described in claim 1, characterized in that, Including the following steps: (s1) In the presence of a first solvent, the polyethyleneimine derivative is reacted with an alkoxysilane to obtain spherical silica, wherein the polyethyleneimine derivative is selected from the group consisting of polyethyleneimine, amidated polyethyleneimine, carboxylated polyethyleneimine, or combinations thereof. (s2) The spherical silica is calcined at 100–700°C to obtain porous grinding beads; and (s3) In the presence of a second solvent, the porous grinding beads react with the first reactant to obtain the grinding beads as described in claim 1; The first solvent is selected from the group consisting of water, ethanol, ammonia, or combinations thereof; The alkoxysilane is selected from the group consisting of tetramethoxysilane, tetraethoxysilane, propoxysilane, or combinations thereof; The second solvent is selected from the group consisting of: water, toluene, ethanol, chloroform, cyclohexane, N,N-dimethylformamide, or combinations thereof; The first reactant is selected from the group consisting of: γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), γ-(aminopropyltriethoxysilane (KH-560), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), hydrochloric acid, succinic anhydride, or combinations thereof.
8. The use of the grinding beads as described in claim 1, characterized in that, Used for sample processing before nucleic acid amplification.
9. A reagent kit, characterized in that, The kit includes the grinding beads as described in claim 1.
10. A method for processing samples, characterized in that, Including the following steps: The grinding beads as described in claim 1 are brought into contact with the sample for sample processing before nucleic acid amplification.